Dehydrogenation of icosahedral carborane anions via gas‐phase collisional activation. (7th April 2016) - Hamdy, Omar M.; Pham, Huong T.; McArthur, Scott G.; Lavallo, Vincent; Julian, Ryan R.
Abstract : Rationale: The icosahedral carborane anion HCB11 H11 –1 is well known for its exceptional stability in solution and the solid state, but the gas‐phase properties of this molecule have not previously been explored. Methods: Electrospray ionization ion trap mass spectrometry, collisional activation, and isotopic labelling were used to examine the formation and reaction pathways of covalent and noncovalent carborane clusters. Results: Covalent attachment of an amino group to the C‐vertex of HCB11 H11 –1 dramatically alters its stability in the gas phase. Interestingly, covalently bound carborane dimers are produced during electrospray ionization. Subsequent collisional activation of these dimers leads to facile hydrogen losses (7 H2 molecules). The loss of H2 does not follow a stochastic pattern, but occurs preferentially by loss of 3 H2, followed by loss of 2 H2 and then another 2 H2 molecules. Conclusions: This study provides insight into new possible modes of B–H activation and functionalization in carborane cages. Copyright © 2016 John Wiley & Sons, Ltd.